Pengaruh Kepemimpinan Terhadap Disiplin Kerja Karyawan Pada PT Adhi Karya (Persero) Tbk Duri - Harwina, Yulia (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research was conducted at PT. Adhi Karya (Persero) Tbk. Thorn. The purpose of this research is to determine the influence of leadership on employee work discipline at PT. Adhi Karya (Persero) Tbk Duri. The population in this study was 342 people. In this research, the sample was taken using a random sampling technique, namely 77 people. The data used is primary and secondary data with analysis using simple linear regression with the equation Y= 10.352+ 0.898X. The research results show that the t_count > t_table (9,968>11.9921) and the Sig. smaller than 0.05 so it can be concluded that there is a significant influence between leadership on employee work discipline at PT. Adhi Karya (Persero) Tbk Duri. The results of the coefficient of determination obtained obtained an R_square value or coefficient of determination of 0.570, which means that the influence of the independent variable/leadership on the dependent variable/employee work discipline is 57.0 percent while the remaining 43.0 percent is influenced by other independent variables which were not observed in the research. such as compensation, work environment, and so on